A novel rhombohedron-like nickel ferrite nanostructure: Microwave combustion synthesis, structural characterization and magnetic properties - G. Suresh Kumar; J. Akbar; R. Govindan; E.K. Girija; M. Kanagaraj (Journal of Science: Advanced Materials and Devices, 2016)
Research on nickel ferrite nanostructures has drawn a great interest because of its inherent chemical, physical and electronic properties. In this study, we have synthesized rhombohedron – like nickel ferrite nanostructure by a rapid microwave assisted combustion method using ethylenediamminetetraacetic acid as a chelating agent. X-ray diffraction, Fourier transform infrared spectrometer, transmission electron microscope and energy dispersive X-ray microanalyser were used to characterize the prepared sample. The magnetic behaviour was analysed by means of field dependent magnetization measurement which indicates that the prepared sample exhibits a soft ferromagnetic nature with saturation magnetization of 63.034 emu/g. This technique can be a potential method to synthesize novel nickel ferrite nanostructure with improved magnetic properties.